Foreword to the special section on Recent Advances in Graphics and Interaction. (February 2022) - Rodrigues, Nuno; Mendes, Daniel; Santos, Luís Paulo; Bouatouch, Kadi
Graphical abstract: Highlights: A novel method for photorealistic rendering of feathers that takes into account their detailed substructures. An analytical tool for cybersecurity puzzle-based training, useful for analyzing players' behavior and game design issues. A review on Multisensory VR/AR in Cultural Heritage, analyzing: evoked stimuli, associated technologies, goals and evaluations. A framework to evaluate remote collaboration supported by AR, including a toolkit for improved data collection and analysis.